Pengaruh Gaya Hidup, Brand Ambassador Dan Harga Produk Terhadap Keputusan Pembelian Konsumen Pada Produk Skincare Skintific : (Studi Pada Konsumen Produk Skintific Semarang) - Pamungkas, Angga Riyan; Wardhani, Masitha Fahmi (Politeknik Negeri Ambon, 2024)
Using quantitative methods, this study aims to explain how lifestyle, brand ambassadors, and product prices influence the purchasing decisions of skincare consumers. This research is a type of associative research. Consumers who have purchased scientific skincare in Semarang are the subjects of this study. In this study, 96 samples were taken from skincare skincare users in Semarang. This study used random sampling using the Lemeshow formula. The results of the T test show that the price of the product and the lifestyle of the Brand Ambassador have a significant influence on purchasing decisions, while the Brand Ambassador does not. Lifestyle variables and product prices influenced purchasing decisions by 47.5%, while other variables influenced 52.5